Potential Implications of Citrulline and Quercetin on Gut Functioning of Monogastric Animals and Humans: A Comprehensive Review - Victoria Anthony Uyanga (MDPI AG, 2021)
The importance of gut health in animal welfare and wellbeing is undisputable. The intestinal microbiota plays an essential role in the metabolic, nutritional, physiological, and immunological processes of animals. Therefore, the rapid development of dietary supplements to improve gut functions and homeostasis is imminent. Recent studies have uncovered the beneficial effects of dietary supplements on the immune response, microbiota, gut homeostasis, and intestinal health. The application of citrulline (a functional gut biomarker) and quercetin (a known potent flavonoid) to promote gut functions has gained considerable interest as both bioactive substances possess anti-inflammatory, anti-oxidative, and immunomodulatory properties. Research has demonstrated that both citrulline and quercetin can mediate gut activities by combating disruptions to the intestinal integrity and alterations to the gut microbiota. In addition, citrulline and quercetin play crucial roles in maintaining intestinal immune tolerance and gut health. However, the synergistic benefits which these dietary supplements (citrulline and quercetin) may afford to simultaneously promote gut functions remain to be explored. Therefore, this review summarizes the modulatory effects of citrulline and quercetin on the intestinal integrity and gut microbiota, and further expounds on their potential synergistic roles to attenuate intestinal inflammation and promote gut health.